OʻZBEKISTONDA EKSPORT SALOHIYATINI OSHIRISHDA TRANSPORT LOGISTIKASINI RIVOJLANTIRISH YOʻNALISHLARI (Marketing Journal, 2026)
AbstractThis study analysed the role of transport logistics in increasing the export potentialof Uzbekistan. Statistical data were used to examine the volume of foreign trade cargo transported by railway and road transport, the condition of logistics infrastructure, andthe dynamics of transport costs. The shares of different transport modes in foreign tradecargo transportation and the changes in export, import, and transit flows wereevaluated. The results demonstrated that modernization of transport infrastructure,development of logistics centers, digitalization of customs procedures, andimprovement of transport service efficiency strengthened export competitiveness. Thestudy substantiated priority directions for developing the national transport andlogistics system aimed at increasing export volumes.Keywords: national income, export, transport logistics, railway, customs,customs duty, subsidy, innovation, trade turnover, investment, macroeconomicstability, investor, gross domestic product, private sector, economic resources, capital.